Enhancing islamic microfinance knowledge and awareness among university students using online talk and mentimeter / Azilawati Banchit ... [et al.] - Banchit, Azilawat; Zainuddin, Puteri Faida Alya; Awang Ahmad, Dayang Ernie Nurfarahain; Mediawati, Elis (Majmuah Enterprise dan UiTM Sarawak, 2022)
The objective of this paper is to gauge and improve the level of knowledge and awareness of University students on Islamic Microfinance Institutions (IMFIs) and functions. Theories in the study of psychology and marketing concur that a person will only adopt a program/new product only after being aware and had attained some knowledge about it. The well-known conventional Microfinance practice or MFIs is a leading tool to eradicate poverty especially in the developing countries like Indonesia but less is known on the level of awareness on the Islamic MFIs (IMFIs) among the university students who will become the future leaders. This study was conducted during an online awareness talk on MFIs in one of the University in West Java, where pre and post questionnaire were shared which were distributed online. Mentimeter, a presentation software was also used during the talk for which their responses were recorded for graphic analysis. Both the statistical and graphic results have indicated high level of knowledge for Islamic Finance concepts but lower awareness among the respondents on IMFIs before the talk. This shows that as a poverty eradication tool, the conventional Microfinance that has the properties of prohibited elements such as riba transactions are widely accepted among the population, especially among these young Muslims adults because they are not aware of the existence of the alternative but mandatory to them, which is the Islamic Microfinance Institutions.